"Silent" β-thalassemia mutation (promoter nt-101 C > T) with increased hemoglobin A2 - Aslan, Deniz (The Turkish Journal of Pediatrics, 2016)
One of the most common silent β-thalassemia mutations is the C > T substitution at position -101 within the distal CACCC box, which leads to a mild reduction in the expression level of the β-globin gene. Carriers of this mutation have a normal hematologic picture without microcytosis and borderline hemoglobin A2 values, and may be missed during screening. Co-occurrence of this mutation with one of the classical β-thalassemia mutations leads to β-thalassemia intermedia, and this is important for Mediterranean populations where β-thalassemia is frequent. Awareness of this mutation, which may have a heterogeneous clinical presentation, is required. We herein present the unusual hematologic findings of a Turkish family carrying this mutation.
Keywords: Silent β-thalassemia mutation (promoter nt-101 C > T); Turkish family; increased hemoglobin A2